Infestation Status of Heart Rot Disease of Pasur (Xylocarpus mekongensis), Tree in the Sundarbans - Helal Siddiqui, A. S. M.; Khair, Abul (Indian Forester, 2012)
The study was conducted to know the heart rot infestation status of Pasur (Xylocarpus mekongensis), trees in the Sundarbans. The tree species is affected by heart rot problem locally known as "dhor". The study showed the highest incidences at Kalabogi (64%) followed by 62% at Bojboja and lowest 17% at Supati (Fresh water zone). It is characterized by the gradual death of the crown, starting first with small twigs and then gradually larger branches die. This is a great loss to the forest ecosystem and the country.